2021
DOI: 10.1007/s11920-021-01293-1
|View full text |Cite
|
Sign up to set email alerts
|

Child and Adolescent Psychosocial Support Programs Following Natural Disasters—a Scoping Review of Emerging Evidence

Abstract: Purpose of Review This review aimed to identify and describe evidence published in the past 3 years from trials of psychosocial support programs for children and adolescents affected by natural disasters. Recent Findings Previous reviews have indicated these programs are beneficial overall. Positive impacts were documented in school-based programs conducted by trained teachers and paraprofessionals with stronger effects achieved by more qualified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Children learnt that their emotions were “ok” and “normal” and they were not the only ones experiencing challenging reactions to the fires. This learning reflects normalisation, an important principle in promoting calming 13,16 . As Hobfoll et al 16 .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Children learnt that their emotions were “ok” and “normal” and they were not the only ones experiencing challenging reactions to the fires. This learning reflects normalisation, an important principle in promoting calming 13,16 . As Hobfoll et al 16 .…”
Section: Discussionmentioning
confidence: 91%
“…This learning reflects normalisation, an important principle in promoting calming. 13,16 As Hobfoll et al 16 observed, "normalising and validating expectable and intense emotional states and promoting survivors' capacities to tolerate and regulate them are important intervention goals" (p. 292).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations